2019
DOI: 10.3390/jcm8122162
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Pump Inhibitors and Hypomagnesaemia in Kidney Transplant Recipients

Abstract: Proton-pump inhibitors (PPIs) are commonly used after kidney transplantation and there is rarely an incentive to discontinue treatment. In the general population, PPI use has been associated with hypomagnesaemia. We aimed to investigate whether PPI use is associated with plasma magnesium, 24-h urinary magnesium excretion and hypomagnesaemia, in kidney transplant recipients (KTR). Plasma magnesium and 24-h urinary magnesium excretion were measured in 686 stable outpatient KTR with a functioning allograft for ≥1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Hypomagnesemia is often experienced in the transplant population due to magnesium wasting as a result of tacrolimus use; PPI use has also been associated with hypomagnesemia 9,33 . With significantly higher rates of magnesium supplementation in the PPI arm, this study added to the body of evidence that PPI use significantly increases hypomagnesemia in the transplant population 15,18–20,25 …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Hypomagnesemia is often experienced in the transplant population due to magnesium wasting as a result of tacrolimus use; PPI use has also been associated with hypomagnesemia 9,33 . With significantly higher rates of magnesium supplementation in the PPI arm, this study added to the body of evidence that PPI use significantly increases hypomagnesemia in the transplant population 15,18–20,25 …”
Section: Discussionmentioning
confidence: 94%
“…9,33 With significantly higher rates of magnesium supplementation in the PPI arm, this study added to the body of evidence that PPI use significantly increases hypomagnesemia in the transplant population. 15,[18][19][20]25 The average time of receipt of PPI or H2RA was several years, despite the majority of patients having no documented GI issues or other compelling reason for therapy posttransplant. At this center, there is a pharmacist present in the outpatient clinic setting but due to high patient volumes not every patient is assessed at every visit by a pharmacist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely documented that PPIs may affect absorption of micronutrients, leading to deficiencies of important electrolytes, including iron and magnesium PLOS MEDICINE [11,14,15]. Indeed, we previously found that PPI use was associated with iron deficiency and hypomagnesemia in KTRs [37,39]. Iron deficiency can in turn lead to iron deficiency anemia, which has been linked to a higher graft failure risk and mortality risk in KTRs [40][41][42].…”
Section: Plos Medicinementioning
confidence: 89%